2008
DOI: 10.1002/env.947
|View full text |Cite
|
Sign up to set email alerts
|

Using different spatial scale measurements in a geostatistically based approach for mapping atmospheric nitrogen dioxide concentrations. Application to the French Centre region

Abstract: SUMMARYPassive sampling surveys followed by geostatistical data analysis have become a common and efficient approach for mapping background concentrations at regional and urban scales. Traffic-related pollution is also a matter of concern as regards population exposure but since it acts at shorter spatiotemporal scales, it is usually not integrated in the same maps. However, to provide more comprehensive information to the authorities and the public, the agencies responsible for air quality monitoring are sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Geostatistics can be used to model data that are spatially and temporally correlated in a statistically rigorous framework . Geostatistics was originally developed in the field of mining, and is now widely used in meteorology, environmental science, and agriculture. A number of studies have demonstrated that geostatistical methods often outperform simpler interpolation methods. Murphy et al used geostatistics for modeling hypoxia in Chesapeake Bay and discussed the advantages of using universal kriging for interpolation . Zhou et al developed a geostatistical model for bottom-water dissolved oxygen (BWDO) in Lake Erie and Obenour et al developed coupled geostatistical models for BWDO and hypoxic thickness to estimate both hypoxic area and volume.…”
Section: Introductionmentioning
confidence: 99%
“…Geostatistics can be used to model data that are spatially and temporally correlated in a statistically rigorous framework . Geostatistics was originally developed in the field of mining, and is now widely used in meteorology, environmental science, and agriculture. A number of studies have demonstrated that geostatistical methods often outperform simpler interpolation methods. Murphy et al used geostatistics for modeling hypoxia in Chesapeake Bay and discussed the advantages of using universal kriging for interpolation . Zhou et al developed a geostatistical model for bottom-water dissolved oxygen (BWDO) in Lake Erie and Obenour et al developed coupled geostatistical models for BWDO and hypoxic thickness to estimate both hypoxic area and volume.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, an industrial station may be highly influenced by the local emissions, thus its scale representativeness may be less than one kilometer. Simultaneous treatments of observations from stations of multiple spatial scales are far from straightforward (Malherbe et al, 2008). Nevertheless, it is improper to strictly relate the scale representativeness to the station typology.…”
Section: Background Stationsmentioning
confidence: 99%
“…In order to provide more comprehensive information to the authorities and the public, the agencies responsible for air quality monitoring are searching for innovative ways of representing background and roadside concentrations together. In recent work, Malherbe et al (199) searched for new ways of jointly representing background and roadside air pollution concentrations by using an approach based on geostatistics and the relationships between seasonal nitrogen dioxide concentrations and auxiliary variables. The approach was applied to data collected in the French Centre region.…”
Section: Environmetricsmentioning
confidence: 99%